Montiscola gen. n., a new alpine genus of Gnophini (Lepidoptera, Geometridae, Ennominae) from Xizang, China, with brachypterous females - Mi, Xiaoye; Han, Hongxiang; Pan, Zhao; Zhu, Chaodong; Cheng, Rui (Zootaxa, 2025)
Montiscola Mi & Cheng gen. nov., a new alpine genus of the tribe Gnophini with brachypterous females, is described from the Kongtanglam Mountain, Jilong, Xizang (Tibet), China, with the support of molecular and morphological evidences, together with its type species Montiscola hongfui Mi & Cheng sp. nov. Morphological characters, including those of the male and female genitalia, are figured and compared with related genera.